Community Adaptation Strategies in the Face of Climate Change for Sustainable Social Development - Rini, Diana Catur; Lestari, Vidia (KnE Social Sciences, 2025)
Climate change has become a pressing global issue with many countries becoming increasingly aware of its impacts. In Indonesia, over 70% of hydrometeorological disasters, such as floods, droughts, biodiversity loss, hails, and landslides, are linked to climate change. One contributing factors is inadequate waste management. This study aims to evaluate the effectiveness of the pentahelix model in mitigating climate change in the village of Kembaran, Tamantirto District, Bantul Regency during 2023–2024. Using a case study approach, the research involves collaboration among academia, businesses, community organizations, government, and media, within the pentahelix framework. The novelty of this research lies in its gender-responsive, community empowerment approach to waste management efforts. The results indicate that the pentahelix model has been effective in improving waste management in Kembaran Village. These findings offer valuable recommendations for policymakers in advancing climate change mitigation, particularly in addressing waste-related issues.